Spinoza: hacia una formación sin modelos (2018)
This text seeks to elaborate an idea of formation in the thought of Baruch de Spinoza, as an alternative to the educational ideas that, in an essentialist way, through the educational process intend to match the student to certain pre-established models. For this, an idea of self-realization is constructed in Spinoza, in which different paths of self-realization for different individuals are desirable. It is proposed that this self-realization consists in being able to act and be affected in many ways, and it is proposed that knowledge in Spinoza implies a certain active passivity that nourishes itself from difference and from the other.